Identification of Adulterated Deer Blood Crystals in Traditional Chinese Medicine Based on MALDI-TOF MS Peptide Fingerprints Technique - Shen-xing WANG; Ling CAO; Qing HUANG; Cong-yu MA; Jian-bin PAN; Hao-dong ZHAO; Hai-wei SHI; Bin DI; Hong-yuan CHEN (Zhipu Xuebao)
This study was focused on analyzing blood crystal products from six species of Chinese medicine deer blood crystals (sika deer, red deer) and commonly adulterated products (pig, cow, sheep, donkey). A method based on matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) combined with chemometric blood analysis was established to identify adulteration in deer blood crystals used in traditional Chinese medicine. In this study, the bottom-up mass spectrometric proteomics approach was applied to acquire the peptide fingerprints of the highly abundant blood proteins, hemoglobin and albumin in samples. The blood crystal samples underwent pretreatments including reduction, alkylation, trypsinolysis, and desalting. Firstly, Skyline software was used to predict candidate peptides by identifying the theoretical characteristic peptides for each species, and the mass spectrometry data of the tryptic digests were collected using ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometer (UPLC-Q-TOF MS). Then, the mass spectrometry data were combined with UNIFI software and Uniprot database to accurately select a set of characteristic peptides that can reflect the differences between the target proteins, which was achieved by examining the presence of candidate characteristic peptides in the samples, as well as considering parameters such as the response, missed cut rate, and detection rate. Thereafter, a one-way controlled variable experiment was conducted to determine the optimal matrix for MALDI-TOF MS analysis. The laser energy was set to 90, and the spotting was performed using the mixing method. α-Cyano-4-hydroxycinnamic acid (CHCA) was identified as the optimal matrix for the blood crystal samples. The optimized MALDI-TOF MS method was employed to obtain the characteristic peptide fingerprints of 10 batches of blood crystals for each of the six species. These fingerprints were then combined with principal component analysis (PCA) in order to achieve rapid and accurate differentiation of blood crystals from different sources. Verification of the method demonstrated that even low abundant adulteration (～10%) in authentic samples can be distinguished. The proposed method has the advantages of high specificity, rapidity, and convenience, which enables sensitive and specific detection of target characteristic peptides in complex matrix samples, and also can provide a highly accurate analytical approach for the identification of adulteration of deer blood crystals and blood crystal-based traditional Chinese medicine products.